Student self-esteem in music education contexts: a systematic literature review - Jiang, Xin; Tong, Yanli (Frontiers in Psychology, 2025)
IntroductionThis systematic literature review (1970–2023) examines how music education relates to students’ self-esteem. Although interest has grown since 1970, evidence remains dispersed across designs and populations.MethodsFollowing the PEO (population, exposure, outcome) framework and PRISMA guidelines, we systematically searched EBSCO, Scopus, and Web of Science. Of 1,332 records identified, we screened empirical studies of students engaged in formal or informal music learning that reported self-esteem outcomes. We extracted trends, methods, measurement tools, and results, and appraised methodological quality.ResultsTwenty-two studies met inclusion criteria (18 quantitative; 4 mixed-methods), with a predominance of cross-sectional designs. Quantitative studies showed stronger methodological quality (mean, x̅ = 0.79), whereas qualitative components of mixed-methods studies were lower (x̅ = 0.43). The Rosenberg Self-Esteem Scale was the most widely used instrument. Across studies, self-esteem in music education was associated with demographic factors (e.g., gender, age) and psychological factors (e.g., self-efficacy). Overall, music learning was linked to enhanced self-esteem among children and adolescents, with notable benefits for specific student groups.DiscussionCurrent evidence indicates a positive relationship between music education and students’ self-esteem; however, generalizability is limited by the dominance of cross-sectional designs and uneven methodological quality. Future research should employ broader designs (e.g., longitudinal and experimental), include more diverse populations, and use consistent, validated measures to strengthen causal inference and applicability.